EFFECT OF RICE BRAN SOURDOUGH ON THE QUALITY OF RICE BRAN LOAF BREAD - Ismiyati; Affandi, Arief Rakhman; Nurdyansyah, Fafa; Ferdiansyah, M. Khoiron (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Sourdough is a fermented mixture of water and flour. Sourdough can be used in making bread with good nutritional content. Instant yeast which is usually used for making bread has adverse effect on health if consumed directly compared to using natural yeast. However, currently sourdough is being developed as a bread developer. This research aims to analyze the effect of the concentration of natural yeast on the physical and chemical characteristics, the shelf life and sensory properties of rice bran bread. The method of this research used a Completely Randomized Design (CRD) with control variables of instant yeast and sourdough concentration of 10%; 20%; 30%; and 40% of the total weight of flour. The tests carried out include the physical quality of the bread, organoleptic tests and proximate content tests. Based on the results of the ANOVA test for texture and color, the same results were obtained so that the best results were determined based on the organoleptic testing, which is rice bran bread with 30% sourdough concentration. Based on proximate analysis, it shows that sourdough rice bran bread has a lower total energy content (195.51 kcal/100g), fat content (3.36%), NaCl content (1.49%), carbohydrate content (26.98%) and reducing sugar (5.39%) also has higher protein content (14.34%) than ricebran bread that uses instant yeast. Sourdough rice bran bread has a longer shelf life compared to rice bran bread using instant yeast.  Keywords: bread, physical and chemical qualities, rice bran, shelf-life, sourdough